Liveness and improficiency in The Clean’s influence upon Dunedin Sound bands - Jorgensen, Darren (Perfect Beat, 2017)
The Clean are a key band in the history of the ‘Dunedin Sound’ of Flying Nun artists from the 1980s. The nature of their influence is however contested by both Dunedin Sound musicians and scholars. This article argues that The Clean’s significance lay in their simulation of improficiency in live performances and recordings. This improficiency is a form of what Philip Auslander calls ‘liveness’, as it represents an attempt to produce authenticity amidst a culture of mediation. The article draws upon accounts of The Clean’s early performances, and on the circumstances within which they produced their first records, to reconstruct the influence of The Clean on Dunedin Sound bands.